SURGICAL OUTCOMES OF CLOSED PEDIATRIC FOREARM SHAFT FRACTURES TREATED WITH KIRSCHNER WIRE FIXATION UNDER FLUOROSCOPIC GUIDANCE AT HAI PHONG CHILDREN’S HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the clinical characteristics, injury patterns, and evaluate the treatment outcomes of closed forearm shaft fractures in children treated with Kirschner wire fixation under fluoroscopic guidance.Subjects and Methods: A retrospective–prospective descriptive study was conducted on 140 pediatric patients treated with Kirschner wire fixation. Variables included epidemiology, injury pattern, surgical characteristics, union time, functional outcomes, and complications.Results: The 6–10 age group accounted for 57.1%, with 69.3% males. Falls were the main cause (39.3%). Both-bone fractures were most common (57.9%), mainly at the midshaft (41.4%). Mean operative time was 40±13.9 minutes; hospital stay 6.8±2.3 days. Union occurred mostly after >8 weeks (42.1%). Good and excellent outcomes reached 92.2% with low complication rates.Conclusion: Kirschner wire fixation under fluoroscopy is a safe and effective method with high union rates and favorable functional outcomes.
Keywords: pediatric forearm fracture; Kirschner wire; fluoroscopy; internal fixation.